The Influence of Work Discipline, Work Environment and Work Motivation on Employee Performance On CV. Bayleaf.id - Lukianti, Riris Anik; Bhirawa, Sigit Wisnu Setya (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim: The aim of this study was to assess whether a partial or combined relationship exists between workplace culture, discipline, and motivation in relation to worker performance on CV. Bayleaf.id. Design/Method/Approach: This study project employs a design of causality and a quantitative methodology. All of the participants in this study were workers at CV.Bayleaf.id. This study involves a targeted selection of 40 respondents through purposive sampling. The analysis incorporates descriptive statistics, hypothesis testing, determination coefficients, multivariate linear regression, and traditional assumption tests using SPSSv27. Research Findings: The findings demonstrated that (1) work motivation, employee performance was impacted by the workplace, work ethics, and both at the same time, and (2) employee performance at CV.Bayleaf.id was positively and greatly influenced by factors related to job work discipline, work atmosphere, and motivation. Theoretical contribution/originality: This research will be useful to help CV. Bayleaf.id and can increase the reader’s insight and knowledge in employee performance, improve discipline, motivation and evaluate the work environment. Practitionel/policy implication: This research provides pract implicatoins for CV. Bayleaf.id in improving employee perfomance. Research limitations: This research has a small scope limitation because it only uses CV.Bayleaf.id as a sample of research objects so that it can beused as a research object.